FACTORS AFFECTING ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON THE ENVIRONMENT OF COMMUNITY ORGANIZATIONS IN INDONESIA - Navis, Maolan Wildan; Widiastuti, Ni Putu Eka; Sumardjo, Mahendro (Universitas Brawijaya, Indonesia, 2020)
The objective of this research is to analyze the influence of all the exogenous variables on organizational citizenship behavior through the organizational culture. This research uses primary data that were obtained by giving the questionnaires directly to the participants of this research as well as using google form. The total number of participants of this research is 75 samples which include people with different positions ranging from syuriah level to MWC level. The method of the research used in this research is multivariate analysis with SEM. The results of this research showed that transformational leadership significantly influenced organizational culture, Transformational Leadership to Organizational citizenship behavior had no significant impact, HR Reposition significantly impacted Organization culture, HR Reposition had a positive and significant influence on organizational citizenship behavior, Spiritual Quotient had a significant effect on Organizational Culture, Spiritual Quotient had a negative and significant effect on organizational citizenship behavior and Organizational citizenship behavior had a positive and significant influence on Organization Culture. For future research, it is advised to take the research time range from 6 to 12 months to get a more complete analysis. And since the scope of research is only PCNU, it is also advised that for further research to do different objects such as PWNU or even PBNU so that the research can result in a distinctive and unique finding that can be compared to the findings of this research.